Cognitive and Affective Insecurity Related to Remaining Employed and Working Conditions: Their Associations With Mental and General Health. Issue 11 (November 2018) - Salas-Nicás, Sergio; Moncada, Salvador; Llorens, Clara; Navarro, Albert
Abstract : Objective: The present study aims to tackle in detail the associations of insecurity with mental and self-rated health by using cognitive and affective measures of insecurity that focus on different aspects such as job loss, difficulties in finding an alternative job, and worsening the working conditions. Methods: Data come from a representative sample of the Spanish salaried working population ( n  = 1807) obtained by the 2016 Psychosocial Risks Survey. Results: Cognitive measures yield stronger associations between job loss and labor market insecurity and health, whereas the association between insecurity over worsening job conditions and health is stronger when using affective measures, the associations with mental health being stronger in both cases than those involving self-rated health. Conclusion: Association with health varies, in strength and at times in direction, depending on how insecurity is measured and conceptualized.